Application of Artificial Intelligence in Cultural Heritage Protection - Li, Junli (Journal of physics. Conference series, 2021)
With the continuous development of science and technology, artificial intelligence has become the subject of extensive discussion in recent years. Artificial intelligence technology uses deep learning to apply this, it shows the trend of high development, such as the previous Go game that shocked the world, the fact that artificial intelligence “Alphago” defeated the world Go champion, people realized that the development of artificial intelligence exceeded people Imagination. Various social industries are gradually introducing artificial intelligence technology to give them new vitality for development. This is exactly how the cultural heritage protection process should be combined with artificial intelligence technology. Cultural protection should enter the digital era, using virtual reality technology and applying segmentation algorithms to segment the prospects of cultural heritage. Complete all aspects of cultural heritage protection without applications. This article introduces the process of artificial intelligence in the protection of cultural heritage using virtual reality technology to realize the digitization of cultural heritage, realizing that the protection of cultural heritage keeps pace with the times. The experimental results of this paper show that the virtual reality technology combined with artificial intelligence is applied to the importance of cultural heritage protection, which improves the vitality of cultural heritage and more perfectly shows the charm of cultural heritage application.